Faith and charity : religion and humanitarian assistance in West Africa - LeBlanc, Marie Nathalie, 1966-; Audet Gosselin, Louis (Anthropology, culture, and society., 2016)
An innovative perspective on the relationship between religion, civil society and development through the prism of faith-based NGOs in West Africa.